Effects of arbuscular mycorrhizal fungi on Solidago canadensis growth are independent of nitrogen form. (7th March 2021) - Song, Dan-Lei; Zhao, Yu-Fei; Tang, Fang-Ping; Zhang, Yan-Hua; Zhou, Shu-Qi; Dong, Li-Jia
Abstract: Aims: Invasive plants may alter soil fungal communities in a way that improves their growth. Nitrogen (N) content of soil affects the symbiosis between plants and arbuscular mycorrhizal fungi (AMF), further determining plant growth. Yet, it is unclear whether altered AMF communities change the dependence of invasive and native species on N-form, and whether N forms alter the invasive plant–AMF interaction (PSIM ). Methods: Two synthetic plant communities, including four Solidago canadensis individuals and four native plant species, were inoculated with AMF spores from S. canadensis -invaded soils and adjacent non-invaded soils, and were provided with nitrate, ammonia or glutamate. After their growth, the performance of the two plant communities in treatments of AMF origin and N forms, and the pathways of the N forms affecting S. canadensis growth and PSIM were evaluated. Important Findings: Solidago canadensis had no obvious N-form dependence in any of the AMF inoculations. Native plant species showed weak N-form dependence, but invasive AMF could remove their N-form dependence. In the absence of N, AMF did not affect growth of S. canadensis and the native plants. In contrast, with N addition, invasive AMF significantly increased belowground and total biomass of the invasive plants but not those of the native plants. Positive PSIM of S. canadensis was also evidently greater than that of native plant species and was realized through directly or indirectly regulating phenotypic traits including plant height, leaf number and number of rhizomes. Our findings emphasize the importance of plant–AMF interactions and a unique N-acquisition strategy during plant invasions.